2017
DOI: 10.1007/s11356-017-9134-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of industrial and domestic ash from biomass combustion, and spent coffee grounds, on soil fertility and plant growth: experiments at field conditions

Abstract: An experimental study was conducted at field conditions in order to evaluate the effect of application of ash from biomass combustion on some soil fertility characteristics and plant growth. Application of 7.5 Mg ha industrial fly ash (IA), domestic ash (DA), and a 50:50 mix of domestic ash (DA) and spent coffee grounds (SCG) was made in different soil parcels. Lolium perenne seeds were sown and the grown biomass was harvested and quantified after 60 days. Soil samples from each parcel were also collected afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 36 publications
2
18
0
1
Order By: Relevance
“…Because ash fertilizers are in regular use in Finland, in the Finnish studies, the harmful elements and nutrient contents of the studied FBCFA were simply compared with the limit values of Finnish legislation. In most studies, a mixture of wood [49,55,[63][64][65] or a mixture of peat and wood [48,50,[52][53][54][59][60][61][62] were used as fuels in the FBC boiler; but in some cases, coal [66][67][68][69][70], sewage sludge [71], agricultural residue [72], swine manure sludge, olive kernel and olive pruning [73] and a co-combustion of sewage sludge and wood [74,75] were studied. Typically, the harmful element contents of the ashes were small and hence were fine for fertilizer use.…”
Section: Fertilizers and Soil Improversmentioning
confidence: 99%
See 1 more Smart Citation
“…Because ash fertilizers are in regular use in Finland, in the Finnish studies, the harmful elements and nutrient contents of the studied FBCFA were simply compared with the limit values of Finnish legislation. In most studies, a mixture of wood [49,55,[63][64][65] or a mixture of peat and wood [48,50,[52][53][54][59][60][61][62] were used as fuels in the FBC boiler; but in some cases, coal [66][67][68][69][70], sewage sludge [71], agricultural residue [72], swine manure sludge, olive kernel and olive pruning [73] and a co-combustion of sewage sludge and wood [74,75] were studied. Typically, the harmful element contents of the ashes were small and hence were fine for fertilizer use.…”
Section: Fertilizers and Soil Improversmentioning
confidence: 99%
“…However, all concentrations of As, Ba Cd, Cr, Cu, Ni, Pb, and Zn were below the limit values for irrigation waters in Portugal. Ribeiro et al [65] studied the effect that biomass FBCFA application has on soil fertility properties and plant growth. FBCFA addition (7.5 Mg/ha, dry basis) increased the soil pH to the recommended value, and the concentrations of Ca, Mg, and K increased in the soil.…”
Section: Field Testsmentioning
confidence: 99%
“…During the roasting process, polymerization of coffee components results in the formation of melanoidins composed of sugars, amino acids, and phenolic compounds, which are not fully characterized due to their structural variations based on roasting temperature and chemical components . Spent coffee grounds are currently used for biodiesel and biogas production, as a precursor for activated carbon, as compost, as an adsorbent for metal ions, and as an alternative for inorganic fertilizers …”
Section: Introductionmentioning
confidence: 99%
“…6 Spent coffee grounds are currently used for biodiesel and biogas production, as a precursor for activated carbon, as compost, as an adsorbent for metal ions, and as an alternative for inorganic fertilizers. 2,[9][10][11][12][13] Many research studies have investigated the health benefits of roasted coffee as a beverage, but few have studied spent coffee grounds. An umbrella analysis of 201 meta-analyses of observational research and 17 meta-analyses of interventional research with roasted coffee indicated the largest relative risk reductions occurred at intakes of three to four cups daily, including all-cause mortality, cardiovascular disease and mortality, and incidence of cancer.…”
mentioning
confidence: 99%
“…The SCGs have been proposed to have a wide range of cosmetics application stemming from its phytochemical composition (e.g., phenolic acids, flavonoids, caffeine) (Campos-Vega et al, 2015). Other possible applications include fertilizers, absorbers, fillers and additives for polymer composites, supplements in animal feed, and biofuels (Givens and Barber, 1986;Castro et al, 2011;Park et al, 2016;Zarrinbakhsh et al, 2016;Moustafa et al, 2017;Ribeiro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%